1991
DOI: 10.1681/asn.v1121289
|View full text |Cite
|
Sign up to set email alerts
|

Plasma oxalate levels rise in hemodialysis patients despite increased oxalate removal.

Abstract: The cause of secondary hyperoxalemia and oxalosis in patients on maintenance dialysis is unknown. The oxalate removal rate was determined in 26 patients on maintenance hemodialysis and 6 on continuous ambulatory peritoneal dialysis by measuring oxalate removed by dialysis and urinary excretion. The role of vitamin B6 deficiency and ascorbate in the raised plasma oxalate concentrations of these patients was evaluated. Plasma oxalate in hemodialysis patients, 442 +/- 41 micrograms/100 mL (mean +/- SE), and perit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In accordance with previous results, the present study demonstrated that UOx excretion or overall oxalate removal levels in all PD patients were within reference intervals for healthy subjects and similar to the previously reported average of UOx excretion in ESKD patients (3,5,6,8,13,35). Nonetheless, the levels of urine output in the participants of the present study were at least four times lower than those of healthy subjects (2,35), meaning that PD patients had hyperoxaluria.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with previous results, the present study demonstrated that UOx excretion or overall oxalate removal levels in all PD patients were within reference intervals for healthy subjects and similar to the previously reported average of UOx excretion in ESKD patients (3,5,6,8,13,35). Nonetheless, the levels of urine output in the participants of the present study were at least four times lower than those of healthy subjects (2,35), meaning that PD patients had hyperoxaluria.…”
Section: Discussionsupporting
confidence: 93%
“…The accumulation of oxalate is associated with oxidative stress and systemic inflammation (1, 8, 9), high cardiovascular risk (9-11), and increased mortality rate (1, 11) in patients with kidney stones and ESKD. Nevertheless, little evidence is available on oxalate balance in ESKD patients in general and peritoneal dialysis (PD) patients in particular; almost all scientific data on this issue were published during the 1980s and 1990s (6,(12)(13)(14).Worldwide, PD is a key element of kidney replacement therapy (15-17). Nonetheless, peritonitis remains one of the major challenges associated with severe clinical complications of PD despite technological advances (17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In one report, three sessions of hemodialysis removed on average of 380 mg of oxalate, although dialyzability could not be estimated [ 131 ]. From studies in dialysis-dependent CKD patients with primary or secondary oxalosis, oxalate clearance surpasses 150 mL/min with hemodialysis and hemodiafiltration [ 301 , 303 305 ], which is at least 300% more than the kidney elimination capacity [ 292 , 297 ]. Oxalate clearance in peritoneal dialysis is consistently less than 8 mL/min [ 139 , 293 , 295 , 296 , 303 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although moderate doses of vitamin C supplementation (up to 1 g/d) are considered safe, vitamin C supplementation is not exempt of potential drawbacks such as oxalosis, of which its appearance would largely depend on initial (pre-intervention) vitamin C status [ 51 , 52 ]. To the best of our knowledge, previous studies (in different clinical settings) have performed randomized supplementation of fixed doses of vitamin C, despite initial vitamin C status.…”
Section: Discussionmentioning
confidence: 99%